ENT600: Oriental electronic taekwondo vest / Aaina Afrina Abd Manaf … [et al.] - Abd Manaf, Aaina Afrina; Abdull Razak, Abdul Halim; Bahrum, Mohammad Asri; Mohd Isa, Nurul Athira; Hashim, Nur Ashikin (2018)
Electronic vest is a new model in taekwondo sport. The system's intelligence is "hidden "inside the vest. The Oriental ETV is an intelligent combination of a pneumatic element fitted to the human body and an ultra-modern electronic system consisting of piezoelectric sensors and high-performance radio technology on a Bluetooth and Radio Frequency Identification. It is designed in such a way that it is tailored exactly to its functions on the human body, taking into consideration body mass, lateral ribs, lower abdominal muscles, upper abdomen, breastbone and back. Therefore, the vest only functions correctly on the human body. Testing it on other objects will give completely unreliable and false results. Accordingly, each vest size is individually calibrated based on sex, body, weight and foot size. The Oriental ETV meets modern technology standards. Athletes will accept the system completely because of the transparent nature of the judging, trainers will refine hitting techniques and judges will face up to the new challenges. This means the way is clear for tournament organisers to make management much simpler, to get people into the halls and in front of the television watching the sport, and therefore to find new sponsors to bring in sources of capital to help the further positive development of the sport. Now it is up to the WTF to give out the right signals.